تطوير محاسبة الوقف الإسلامي في ضوء معايير الإبلاغ المالي الدولية - بومدين، نورين Boumadian, Nourin; هنى، محمد أحمد جعفر (جامعة عمار ثليجي الأغواط - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2019)
تزايدت مطالبات المحاسبة على الوقف الإسلامي، بما يكفل الشفافية والإفصاح والمساءلة وتحديد المسؤولية، والتأكد من تقيد إدارة الوقف بالأحكام الشرعية، والقوانين والنظم المعمول بها، ومعايير السلوك، والأخلاق الإسلامية وكافة الضوابط الخاصة بالوقف، بما يسهم في حفظ الوقف وأصوله وممتلكاته، وحقوق الموقوف عليهم، ويبث الثقة في الوقف، ويخلق صورة إيجابية عنه لدى المجتمع، ويسهم في حماية الوقف من المخاطر الناتجة عن سوء الإدارة. تهدف الدراسة إلى تطوير نموذج لتفاعل الأسس والممارسات المحاسبية في الإطار العام لنظام الإدارة في المؤسسات الوقفية لضبط أنشطتها وضمان حسن استخدامها للأموال الموقوفة. وقد توصلت الدراسة إلى أن النموذج المحاسبي المقترح لقياس وتوزيع الريع في المؤسسات الوقفية يحقق الإفصاح الواضح لكافة القواعد والأسس والضوابط التي يقوم عليها هذا النموذج، مما يدفع إلى زيادة الوعي لما تقوم به المؤسسات الوقفية.
Accountability has Increased on Islamic Waqf claims, in order to ensure transparency, disclosure and accountability and determine responsibility, and make sure Endowment Management restrict Sharia, laws and regulations, and standards of conduct, and the Islamic ethics and all private cessation controls, including contributing to the conservation endowment, assets and property, the rights of detained them and inspire confidence in the wakf, and creates a positive image about the community, and contribute to the protection of cessation of risks resulting from mismanagement. The study aims to develop a model for the interaction of accounting foundations and practices in the general framework of the management system in the waqf institutions to control their activities and ensure their proper use of the suspended funds. The study concluded that the proposed accounting model for the measurement and distribution of rents in waqf institutions achieves a clear disclosure of all the rules, bases and controls on which this model is based, thus raising awareness of the work of waqf institutions.
Keywords: الوقف الإسلامي -- الأحكام الشرعية -- الأخلاق الإسلامية -- المؤسسات الوقفية -- السياسة المحاسبية